Effects of Maternal Subclinical Hypothyroidism in Early Pregnancy Diagnosed by Different Criteria on Adverse Perinatal Outcomes in Chinese Women With Negative TPOAb - Li, Mei-Fang; Ma, Li; Feng, Qi-Ming; Zhu, Yue; Yu, Tian-Pei; Ke, Jiang-Feng; Zhang, Zhi-Hui; Liu, Yun; Li, Lian-Xi (Frontiers in Endocrinology, 2020)
Aims: To compare the effects of maternal subclinical hypothyroidism (SCH) diagnosed by the 2011 or 2017 “Guidelines of the American Thyroid Association (ATA) for the diagnosis and management of thyroid disease during pregnancy and the postpartum” during the first trimester on adverse pregnancy outcomes in thyroid peroxidase antibody (TPOAb)–negative pregnant women. Methods: There were 1,556 Chinese singleton pregnant women with negative TPOAb diagnosed with either SCH or euthyroidism who were investigated, and the prevalence and risk of obstetric outcomes were compared between the two groups using 2011 and 2017 ATA standards, respectively. The effects of a mildly elevated thyroid-stimulating hormone (TSH) concentration on adverse pregnancy outcomes were evaluated by binary logistic regression. Results: Maternal SCH identified by the 2011 ATA guidelines correlated with higher rates and risks of pregnancy-induced hypertension (PIH), preeclampsia, and low-birth-weight infants, while maternal SCH diagnosed by the 2017 ATA guidelines was more likely to develop PIH, preeclampsia, cesarean delivery, preterm delivery, placenta previa, and total adverse maternal and neonatal outcomes. Moreover, a mildly elevated TSH level was significantly associated with PIH after adjustment for confounding factors. Conclusions: Compared with the 2011 ATA guidelines, the 2017 ATA guidelines could be more applicable to Chinese pregnant women to screen the effects of SCH on the majority of adverse pregnancy outcomes.